Adjuvant intraperitoneal ceftriaxone in the treatment of septic peritonitis in horses - Alonso, Juliana De Moura [UNESP]; Rosa, Gustavo Dos Santos [UNESP]; Santos, Bruna [UNESP]; Guerra, Simony [UNESP]; Ribeiro, Márcio [UNESP]; Watanabe, Marcos Jun [UNESP]; Alves, A. [UNESP]; Rodrigues, Celso [UNESP]; Takahira, Regina Kiomi [UNESP]; Hussni, Carlos Alberto [UNESP] (Wiley, 2020)
Background Intraperitoneal administration of ceftriaxone maintains therapeutic abdominal concentrations for 24 hours in healthy horses. Therefore, it is a possible treatment for septic peritonitis. The aim of this study was to evaluate the efficacy of ceftriaxone as an adjuvant treatment in horses with septic peritonitis. Methods Twenty-six horses with clinical signs, sonography and/or laboratory findings of septic peritonitis were included. Peritoneal fluid was collected for microbiological culture and in vitro microbial sensitivity profile assessment. Daily intraperitoneal administration of ceftriaxone (25 mg/kg) was initiated with supportive and systemic antimicrobial treatment. The animals were divided into three groups: group 1 - gastrointestinal tract injuries and abdominal surgery (excluding perforations/ruptures); group 2 - not related to changes in the gastrointestinal tract; group 3 - secondary to intestinal rupture and/or faeces contamination. Results The mean success rate of the treatment was 77 per cent (20/26 animals), with success rates of 84.6 per cent in group 1; 87.5 per cent, group 2; and 40 per cent, group 3. Conclusions This is the first study to report adjuvant intraperitoneal treatment ceftriaxone for septic peritonitis in horses and indicates that this treatment can successfully treat septic peritonitis in horses.
Keywords: antimicrobials; cephalosporins; horses; peritoneum